Influence of School Climate on Teachers’ Turnover Intention in Public and Private Primary Schools, Ikeja City, Lagos Nigeria - Ittai, Joy; Ogunji, James (European Scientific Journal, ESJ, 2024)
Teacher career turnover is a serious global occupational hazard in many countries, with the estimated teacher turnover rate ranging from 13 to 15% annually. There cannot be actual turnover without turnover intentions which is a key precursor. Being multilevel structured phenomenon, several school variables could be implicated such as school climate and job satisfaction. Consequent to the dearth of literature in this regards in Lagos state Nigeria, this research work used a survey research design to study this phenomenon in public and private primary schools. A total of 373 teachers were sampled through a simple random technique and data collected with structured questionnaire. Appropriate descriptive and inferential statistics such as Pearson product moment correlations, simple linear regression, Independent T-Test were used to analyze the data. The findings revealed there was a significant influence of school climate of public and private primary schools teachers’ turnover intention. The study indicated that the school climate measures (safety, academic climate, community climate and organizational environment) jointly influence teachers thinking of quitting their current job (R= .606, Adj. R2=.361, F (4, 367) = 53.336. p <0.05), searching for another job (R= .622, Adj. R2=.380, F (4, 368) = 58.024. p <0.05) or obtaining employment letter for another job (R= .668, Adj. R2=.441, F (4, 364) = 73.476. p <0.05). The study concluded in view of the data analyzed that school type (public or private primary schools’ climate) has a significant, moderating effect on teachers’ turnover intention. Teachers’ turnover intention was higher in private schools in Ikeja city primary schools. It is recommended that public and private primary schools in Ikeja city should intentionally improve school climate by improving safety, academic climate, community climate and organizational environment to reduce teacher turnover intention.